Copper‐Catalyzed C3−H Difluoroacetylation of Quinoxalinones with Ethyl Bromodifluoroacetate. Issue 10 (4th April 2019) - Wang, Liping; Liu, Hongyun; Li, Fanfan; Zhao, Jiquan; Zhang, Hong‐Yu; Zhang, Yuecheng
Abstract: A copper‐catalyzed direct C−H difluoroacetylation of quinoxalinones at the C‐3 position with ethyl bromodifluoroacetate has been developed. In this reaction, diverse difluoroacetylated quinoxalin‐2(1 H )‐ones with a wide range of functional groups could be obtained in moderate to good yields, using cheap, commercially available reagents. This protocol would offer a meaningfully synthetic method for pharmacologically interesting difluoroacetylated quinoxalin‐2(1 H )‐one derivatives. Abstract :